Electro-adsorption as a Hybrid Processing to Removed Oil from Synthetic Oily Solution by Using Activated Carbon and Iron Electrodes - Lia Cundari; Bazlina Dawami Afrah; Suci Dwijayanti; Alvina Suryadinata; Aldi Ramadhani (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2022)
Biosolar contains oil, fatty acids, emulsifiers, bactericides, and other chemicals. If the oil contents are mixed with water, it will become hazardous waste and affect drinking water sources, endanger human health, air pollution, affect agricultural production, and damage the natural landscape, so the oil content must be processed to reduce its hazardous content. One of the methods used in treating oily solutions is adsorption. The adsorption method for oily solution treatment is ineffective because it requires several stages, so the required capital is relatively larger and takes longer. Electro-adsorption is one of the methods that is being developed for treating oily solutions. Electro-adsorption is a hybrid separation technology to break down oil emulsions in wastewater and some other organic content. The purpose of this study is to characterize the activated carbon and determine the effect of voltage and time on synthetic oily solution treatment in terms of COD value and oil-fat content. A synthetic oily solution is made by mixing 1 g of biosolar/B30 into the water from the Musi River to a volume of 1 L. The application of the electro-adsorption method uses commercially activated carbon as an adsorbent and iron as an electrode. Variations given to the process with voltage 0, 5, 10, 15 V and time 0, 5, 10, 15, 20, and 25 minutes. The characteristic of activated carbon showed a size change in the pore size from 2.58 µm to 1.98 µm and a reduction of surface area from 740 (±180) m2/g to 730 (±120) m2/g. The electro-adsorption method was effective in treating oily solutions. The decrease of COD reaches the maximum level at a voltage 10 V for 25 minutes, which was 75.92% from 62.33 mg/L to 15 mg/L initially, while the concentration of oil-fat obtains the maximum level at a voltage of 5 V for 5 minutes that is equal to 99.65%, initially 303.19 mg/L to 1.05 mg/L. The optimum condition of the electro-adsorption process in synthetic oily solution was at the voltage of 5 V and a time of 5 minutes. The electro-adsorption process is an effective method to treat synthetic oily solutions.